Schrödinger equation with gauge-invariant field-impulse replacing potentials and computation using LOD-FDTD method - Eng Leong Tan; Ding Yu Heh (Computer Physics Communications, 2026)

Identification of flavonoid-producing endophytic fungi isolated from Ficus hirta Vahl. and their bioactive properties - Jing Li; Wanjia Yan; Sunjing Tan; Peng Shao; Xia Li; Xinhong Dong; Jian Sun; Hock Eng Khoo (Food Bioscience, 2025)

Analysis and assessment of natural ventilation in the design of urban precincts using an overset grid CFD approach - Vinh-Tan Nguyen; Bharathi Boppana; Jason Leong; Hee Joo Poh; Yong Eng; Irene Lee; Hwee Sien Tan (Building and Environment, 2025)

A review on laser-induced graphene in flexible energy storage: From materials selection to biomedical applications - Soon Poh Lee; Pei Song Chee; Chun Hui Tan; Kwok Feng Chong; Eng Hock Lim; Cao Guan (Chemical Engineering Journal, 2024)

Comments on “Association of environmental tobacco smoke exposure with chronic constipation: a nationwide survey (NHANES 2005–2010)” Duan R, et. al., doi (10.1007/s11356-023–30542-4) - Brendan Jen-Wei Tan; Zhi-Dong Zhou; Ling-Ling Chan; Eng-King Tan (Environmental Science and Pollution Research, 2024)

A machine-learning exploration of the exposome from preconception in early childhood atopic eczema, rhinitis and wheeze development - Yizhi Dong; Hui Xing Lau; Noor Hidayatul Aini Suaini; Michelle Zhi Ling Kee; Delicia Shu Qin Ooi; Lynette Pei-chi Shek; Bee Wah Lee; Keith M. Godfrey; Elizabeth Huiwen Tham; Marcus Eng Hock Ong; Nan Liu; Limsoon Wong; et al. (Environmental Research, 2024)

Regional ionospheric TEC modeling during geomagnetic storm in August 2021- data fusion using multi-instrument observations - Suneetha Emmela; D. Venkata Ratnam; Tan Eng Leong (Advances in Space Research, 2024)

Simulated transmission and decontamination of Listeria monocytogenes biofilms from plastic cutting boards - Ali Yassoralipour; Jun Xian Wong; Wen Han Chow; Sook Ngoh Chen; Chee Hao Kuan; Eng Tong Phuah; Ji Tan; Tsun-Thai Chai (Food Control, 2023)

An integrated life-cycle greenhouse gas protocol accounting on oil palm trunk and empty fruit bunch biofuel production - Zhen Li Chew; Eng Hau Tan; Sathiamurthy A.L. Palaniandy; Kok Sin Woon; Zhen Xin Phuang (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Medium chain triglyceride and medium-and long chain triglyceride: metabolism, production, health impacts and its applications – a review - Yee-Ying Lee; Teck-Kim Tang; Eng-Seng Chan; Eng-Tong Phuah; Oi-Ming Lai; Chin-Ping Tan; Yong Wang; Nur Azwani Ab Karim; Noorlida Habi Mat Dian; Joo Shun Tan (Critical Reviews in Food Science and Nutrition, 2022)

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

The reaction of wastewater treatment and power generation of single chamber microbial fuel cell against substrate concentration and anode distributions - Sing-Mei Tan; Soon-An Ong; Li-Ngee Ho; Yee-Shian Wong; Wei-Eng Thung; Tean-Peng Teoh (Journal of Environmental Health Science and Engineering, 2020)

Production, safety, health effects and applications of diacylglycerol functional oil in food systems: a review - Yee-Ying Lee; Teck-Kim Tang; Eng-Tong Phuah; Chin-Ping Tan; Yong Wang; Ying Li; Ling-Zhi Cheong; Oi-Ming Lai (Critical Reviews in Food Science and Nutrition, 2020)

Current Opinions and Consensus for Studying Tremor in Animal Models - Sheng-Han Kuo; Elan D. Louis; Phyllis L. Faust; Adrian Handforth; Su-youne Chang; Billur Avlar; Eric J. Lang; Ming-Kai Pan; Lauren N. Miterko; Amanda M. Brown; Roy V. Sillitoe; Collin J. Anderson; et al. (The Cerebellum, 2019)

Overview of Urethral Reconstruction by Tissue Engineering: Current Strategies, Clinical Status and Future Direction - Zahra Rashidbenam; Mohd Hafidzul Jasman; Pezhman Hafez; Guan Hee Tan; Eng Hong Goh; Xeng Inn Fam; Christopher Chee Kong Ho; Zulkifli Md Zainuddin; Reynu Rajan; Fatimah Mohd Nor; Mohamad Aznan Shuhaili; Nik Ritza Kosai; et al. (Tissue Engineering and Regenerative Medicine, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Automated analysis of gait and modified timed up and go using the Microsoft Kinect in people with Parkinson’s disease: associations with physical outcome measures - Dawn Tan; Yong-Hao Pua; Shaminian Balakrishnan; Aileen Scully; Kelly J. Bower; Kumar Manharlal Prakash; Eng-King Tan; Jing-Si Chew; Evelyn Poh; Siok-Bee Tan; Ross A. Clark (Medical & Biological Engineering & Computing, 2019)

Multiple locus genome-wide association studies for important economic traits of oil palm - Maizura Ithnin; Yang Xu; Marhalil Marjuni; Norhalida Mohamed Serdari; Mohd Din Amiruddin; Eng-Ti Leslie Low; Yung-Chie Tan; Soon-Joo Yap; Leslie Cheng Li Ooi; Rajanaidu Nookiah; Rajinder Singh; Shizhong Xu (Tree Genetics & Genomes, 2017)

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

Erratum to: Mitochondrial CHCHD-Containing Proteins: Physiologic Functions and Link with Neurodegenerative Diseases - Zhi-Dong Zhou; Wuan-Ting Saw; Eng-King Tan (Molecular Neurobiology, 2017)

Mitochondrial CHCHD-Containing Proteins: Physiologic Functions and Link with Neurodegenerative Diseases - Zhi-Dong Zhou; Wuan-Ting Saw; Eng-King Tan (Molecular Neurobiology, 2017)

FUS-linked essential tremor associated with motor dysfunction in Drosophila - Murni Tio; Rujing Wen; Yih Lin Lim; Huashan Wang; Shuo-Chien Ling; Yi Zhao; Eng-King Tan (Human Genetics, 2016)

Pharmacogenetic effects of regulatory nuclear receptors (PXR, CAR, RXRα and HNF4α) on docetaxel disposition in Chinese nasopharyngeal cancer patients - Sin-Chi Chew; Joanne Lim; Onkar Singh; Xiangai Chen; Eng-Huat Tan; Edmund-JD Lee; Balram Chowbay (European Journal of Clinical Pharmacology, 2014)

Next-generation sequencing diagnostics for neurological diseases/disorders: from a clinical perspective - Jia Nee Foo; Jianjun Liu; Eng-King Tan (Human Genetics, 2013)

Synaptic conditions for auto-associative memory storage and pattern completion in Jensen et al.’s model of hippocampal area CA3 - Eng Yeow Cheu; Jiali Yu; Chin Hiong Tan; Huajin Tang (Journal of Computational Neuroscience, 2012)

Proteomic analysis of cell suspension cultures of Boesenbergia rotunda induced by phenylalanine: identification of proteins involved in flavonoid and phenylpropanoid biosynthesis pathways - Eng Chong Tan; Saiful Anuar Karsani; Gen Teck Foo; Sher Ming Wong; Noorsaadah Abdul Rahman; Noorzulaani Khalid; Shatrah Othman; Rohana Yusof (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Comparison of phenotypic methods and matrix-assisted laser desorption ionisation time-of-flight mass spectrometry for the identification of aero-tolerant Actinomyces spp. isolated from soft-tissue infections - L. S. Y. Ng; J. H. C. Sim; L. C. Eng; S. Menon; T. Y. Tan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

GWAS-linked GAK locus in Parkinson’s disease in Han Chinese and meta-analysis - Nan-Nan Li; Xue-Li Chang; Xue-Ye Mao; Jin-Hong Zhang; Dong-Mei Zhao; Eng-King Tan; Rong Peng (Human Genetics, 2012)

Sun exposure and risk of lymphoid neoplasms in Singapore - Kin-Yoke Wong; Bee-Choo Tai; Sin-Eng Chia; Ponnudurai Kuperan; Khai-Mun Lee; Soon-Thye Lim; Susan Loong; Benjamin Mow; Siok-Bian Ng; Leonard Tan; Soo-Yong Tan; Suat-Hoon Tan; et al. (Cancer Causes & Control, 2012)

Evaluation of the cytotoxic and inflammatory potential of differentially shaped zinc oxide nanoparticles - Boon Chin Heng; Xinxin Zhao; Eng Chok Tan; Nurulain Khamis; Aarti Assodani; Sijing Xiong; Christiane Ruedl; Kee Woei Ng; Joachim Say-Chye Loo (Archives of Toxicology, 2011)

Shogaols at proapoptotic concentrations induce G2/M arrest and aberrant mitotic cell death associated with tubulin aggregation - Fei-Fei Gan; Amrita A. Nagle; Xiaohui Ang; Olivia Huixian Ho; Sock-Hoon Tan; Hong Yang; Wai-Keung Chui; Eng-Hui Chew (Apoptosis, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

SSR mining in oil palm EST database: application in oil palm germplasm diversity studies - Ngoot-Chin Ting; Noorhariza Mohd Zaki; Rozana Rosli; Eng-Ti Leslie Low; Maizura Ithnin; Suan-Choo Cheah; Soon-Guan Tan; Rajinder Singh (Journal of Genetics, 2010)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Thiopurine S-methyltransferase activity in three major Asian populations: a population-based study in Singapore - Shirley Kow Yin Kham; Chin Kok Soh; Te Chih Liu; Yiong Huak Chan; Hany Ariffin; Poh Lin Tan; Allen Eng Juh Yeoh (European Journal of Clinical Pharmacology, 2008)

Exploiting an oil palm EST database for the development of gene-derived SSR markers and their exploitation for assessment of genetic diversity - Rajinder Singh; Noorhariza Mohd Zaki; Ngoot-Chin Ting; Rozana Rosli; Soon-Guan Tan; Eng-Ti Leslie Low; Maizura Ithnin; Suan-Choo Cheah (Biologia, 2008)

Intragenic linkage disequilibrium structure of the human perilipin gene (PLIN) and haplotype association with increased obesity risk in a multiethnic Asian population - Lu Qi; E. Shyong Tai; Chee Eng Tan; Haiqing Shen; Suok Kai Chew; Andrew S. Greenberg; Dolores Corella; Jose M. Ordovas (Journal of Molecular Medicine, 2005)